2017
DOI: 10.1155/2017/7121785
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Effect on Structural Interaction between Energy Pile and Its Host Soil

Abstract: Energy pile is one of the promising areas in the burgeoning green power technology; it is gradually gaining attention and will have wide applications in the future. Because of its specific structure, the energy pile has the functions of both a structural element and a heat exchanger. However, most researchers have been paying attention to only the heat transfer process and its efficiency. Very few studies have been done on the structural interaction between the energy pile and its host soil. As the behavior of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…When the pile is heated or cooled, the contact between the soil and the pile will change, which leads to a change in the pile-soil load transferring mechanism [23][24][25][26]. It was found that the soli-concrete interface was affected by cyclic degradation, but not affected directly by temperature.…”
Section: Introductionmentioning
confidence: 99%
“…When the pile is heated or cooled, the contact between the soil and the pile will change, which leads to a change in the pile-soil load transferring mechanism [23][24][25][26]. It was found that the soli-concrete interface was affected by cyclic degradation, but not affected directly by temperature.…”
Section: Introductionmentioning
confidence: 99%